Mongolia Quarterly Economic Update, January 2011 - World Bank (Washington, DC, 2017)
The economy continues to recover with most sectors rebounding strongly from the sharp drop in output late 2008 and early 2009. Preliminary estimates suggest that real Gross Domestic Product (GDP) grew by 6.1 percent year-on-year in 2010, following an outturn of minus 1.3 percent in 2009. However, winter arrived in Mongolia with the agriculture sector still feeling the impact from last year's dzud. The sector has now experienced double-digit contractions for the third quarter in a row. The exchange rate against the US dollar has been slowly appreciating back to the pre-crisis level. In December 2010, the average monthly exchange rate against the US$ appreciated by 3.0 percent, compared to the previous month, or 15 percent compared to December 2009. The latest survey conducted in informal labor markets in December 2010 revealed a reduction in number of casual workers by about 40 percent compared to September due to the seasonal closure of construction labor markets, and reduced outdoor sales activities due to cold weather. Mongolia has made significant progress in improving budget transparency, but there is still considerable room for improvement. Finally, although Mongolia's laws are easily accessible online and court processes are generally impartial and transparent, the predictability of court decisions is limited and the courts, enforcement and registration agencies are often perceived as corrupt by the public.